Danish rocked my world - Morris, Corey (Language at Work - Bridging Theory and Practice, 2008)
My life took an unexpected twist when I fell in love with a Dane and moved to Denmark. Faced with mastering the next to impossible Danish language, my modern day fairytale quickly turned into one of the most challenging epochs of my life.